1985
DOI: 10.1038/315232a0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of T-cell antigen receptor genes during fetal development in the thymus

Abstract: The T-cell antigen receptor is a heterodimeric molecule composed of alpha- and beta-subunits of relative molecular mass 40,000-50,000 (refs 1-6). Recently, the genes encoding both the beta- and alpha- chains have been cloned. By comparing amino-acid and nucleic-acid sequences, it is clear that these genes encode the alpha- and beta-proteins of the T-cell receptor. In addition, a third receptor-like gene, the gamma-chain gene, has been identified, which has many structural and sequence characteristics in common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
100
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(109 citation statements)
references
References 30 publications
9
100
0
Order By: Relevance
“…Moreover, Northern analysis of thymus RNA revealed only the expression of a 1.0-kb TCR-fl message from normal and irradiated RAG-2-/-mice (data not shown). The 1.0-kb message has been reported to correspond to a germline-sterile transcript or to an incomplete D-J rearrangement of the TCR-B loci, which appears early in T cell development and which may precede full V-D-J rearrangement (16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Northern analysis of thymus RNA revealed only the expression of a 1.0-kb TCR-fl message from normal and irradiated RAG-2-/-mice (data not shown). The 1.0-kb message has been reported to correspond to a germline-sterile transcript or to an incomplete D-J rearrangement of the TCR-B loci, which appears early in T cell development and which may precede full V-D-J rearrangement (16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…In mice and also humans, the majority of T cells developing in the thymus express the § g TCR on their surface, and the antigen recognition structure of both the TCR § and TCR g chains is produced through the rearrangement of segments of these genes [1,2]. It has been shown that rearrangement of the TCR g gene precedes that of the TCR § genes [3,4]. Cells that have succeeded in in-frame rearrangement of the TCR g gene express the TCR g chain together with the pre-TCR § chain [5], and then proliferate extensively prior to TCR § gene rearrangement [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The most immature population of thymocytes is generally defined as double negative (DN) or pro-T cells, which reflects the fact that they still do not express the co-receptor genes CD4 and CD8 which cooperatively with TCR bind to conserved regions of MHC class II and MHC class I molecules, respectively 7,8 . The DN thymocytes migrate from the cortico-medullary junction towards the outer cortex 9 and during migration through the thymic tri-dimensional meshwork, DN cells are induced to start the process of somatic gene rearrangements 10 . Concomitantly with migration and maturation of DN population the changes in expression pattern of cell surface molecules (CD44 and CD25) take place on the basis of which the DN maturation process can be monitored.…”
Section: Early Events In T Cell Development and Positive Selectionmentioning
confidence: 99%